Management of a Low-Energy Penetrating Brain Injury Caused by a Nail - V. R. Ferraz; G. B. Aguiar; J. L. Vitorino-Araujo; G. L. Badke; J. C. E. Veiga (Case Reports in Neurological Medicine)
Low-energy penetrating nail injury to the brain is an extremely rare neurosurgical emergency. The most common cause of nail gun injury is work related accidents; other causes result from accidental firing of a nail gun, suicide attempts by firing nail guns into the brain, and bomb blasts containing pieces of nails. Neurosurgical treatment performed by craniotomy still seems to be the safest one; there are reports of complications such as subdural hematoma and intraparenchymal hemorrhages following the blind removal of foreign bodies leading to suggestions that all penetrating foreign bodies should be removed under direct vision. We report a rarely described neurosurgical approach for removal of a penetrating nail from the brain and skull without evidence of associated hematoma and other brain lesions.